Forensic acpects of alcohol abuse and homicide - Žarković-Palijan, Tija (Array, 2009)
Abstract: Numerous investigations indicate a close link between violent behavior, homicide (murder) and alcohol intoxication. With increased frequency of drinking and the chronic consummation of alcohol, the risk of the fatal outcome or homicide and victimization caused by violence is more likely to occur. Studies conducted on convicted murderers suggested that about half of them were under the heavy influence of alcohol at the time of perpetration of murder. The sample in this survey consisted of 177 male offenders which committed criminal act of murder in Croatia from the year of 1990 until 2007 (capital murder and attempted murder). All were assigned for the forensic psychiatric evaluation by the Criminal Justice System (Court of Law) at the Department of Forensic Psychiatry, Neuropsychiatric Hospital, Popova~a, Croatia. For the purpose of this work the sample is divided in two groups of subjects: 1) offenders which were intoxicated at the time of murder and committed offence on intoxicated victim 2) offenders who were sober and committed offence on sober victims. Groups are compared according to the variables of crime and history of alcohol abuse. On the basis of obtained results we can conclude that there are significant differences in relation to the variables and modalities of criminal offence between two groups of offenders and victims. We could conclude that alcohol intoxication in offenders and victims at the time of murder could strongly affect the modalities of murder